Różnice indywidualne w nabywaniu kompetencji pragmatycznej przez nauczycieli języka angielskiego - Szczepaniak-Kozak, Anna; Wąsikiewicz-Firlej, Emilia (Neofilolog, 2017)
Acquisition of pragmatic competence (PC) in a foreign language is a gradual process, which is not trouble-free and effortless even for advanced learners. Since most of the existing research on PC has focused on learners of English, this paper constitutes an attempt to investigate this matter from the perspective of foreign language teachers, with particular attention paid to teachers of English in Poland. Its aim is to investigate whether individual differences influence the acquisition of PC on the basis of data collected during classroom observations and in interviews with teachers. This way the authors endeavor to answer the question whether PC of the teachers depends on their general linguistic ability in English, their educational background and teacher preparation, or the stage of their career development.